2000
DOI: 10.1126/science.289.5481.957
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of Glutamate into Synaptic Vesicles by an Inorganic Phosphate Transporter

Abstract: Previous work has identified two families of proteins that transport classical neurotransmitters into synaptic vesicles, but the protein responsible for vesicular transport of the principal excitatory transmitter glutamate has remained unknown. We demonstrate that a protein that is unrelated to any known neurotransmitter transporters and that was previously suggested to mediate the Na(+)-dependent uptake of inorganic phosphate across the plasma membrane transports glutamate into synaptic vesicles. In addition,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
628
1
18

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 731 publications
(682 citation statements)
references
References 43 publications
35
628
1
18
Order By: Relevance
“…The glutamatergic synapses of the cerebellar cortex were recognized on the basis of the topographic distribution in the cerebellar cortex layers and expression of vesicular glutamate transporters, vGluT-1 and/or vGluT-2 [39,40,58-62]. In the present study, we observed that the glutamatergic synapses between the parallel fibre terminals and the dendritic tree of Purkinje neurons frequently display co-localization of vGluT-1 with the three SNARE proteins examined.…”
Section: Discussionmentioning
confidence: 50%
“…The glutamatergic synapses of the cerebellar cortex were recognized on the basis of the topographic distribution in the cerebellar cortex layers and expression of vesicular glutamate transporters, vGluT-1 and/or vGluT-2 [39,40,58-62]. In the present study, we observed that the glutamatergic synapses between the parallel fibre terminals and the dendritic tree of Purkinje neurons frequently display co-localization of vGluT-1 with the three SNARE proteins examined.…”
Section: Discussionmentioning
confidence: 50%
“…The first of these to be identified, VGLUT1, was assigned as a vesicular glutamate transporter after having first been identified as an inorganic phosphate carrier. 358,359 Subsequently, VGLUT2 and VGLUT3 were cloned and characterized and shown to have distinctive distributions in the brain. These transporters have a much lower affinity for glutamate than EAAT1-5 and, unlike the plasma membrane transporters, they do not transport Dand L-aspartate.…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%
“…VGlut1 was previously named the brain, Nadependent Pi (BNPI) transporter because of its homology to inorganic phosphate transporters in the kidney. However, subsequent experimentation established that VGlut1, 2 and 3 are present on vesicular membranes and function as glutamate transporters (Bellocchio et al, 2000;Takamori et al, 2000). By contrast with the plasma membrane glutamate transporters (Eliasof et al, 1998), vesicular glutamate transporters are sodium-independent and exhibit a more than 10-fold lower Km (2 mM: Bellocchio et al, 2000).…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%
“…However, subsequent experimentation established that VGlut1, 2 and 3 are present on vesicular membranes and function as glutamate transporters (Bellocchio et al, 2000;Takamori et al, 2000). By contrast with the plasma membrane glutamate transporters (Eliasof et al, 1998), vesicular glutamate transporters are sodium-independent and exhibit a more than 10-fold lower Km (2 mM: Bellocchio et al, 2000). In place of sodium-dependence, glutamate uptake into vesicles relies primarily on the electrical component (ΔΨ) of the electrochemical gradient across the vesicle membrane.…”
Section: Vesicular Glutamate Transportersmentioning
confidence: 99%
See 1 more Smart Citation